Clarifying the roles of marketing and sales - Le Meunier-FitzHugh, Kenneth (Henry Stewart Talks, 2010)
Exploring the sales and marketing relationship, Historically sales and marketing have been seen as a single functional area, but they have developed very different specialist skills, perspectives and cultures, Problems in the sales and marketing relationship, How to improve collaboration between sales and marketing, The importance of the sales and marketing interface in creating superior business performance